Film-Forming Sprays for Topical Drug Delivery - Umar AK; Butarbutar M; Sriwidodo S; Wathoni N (Dove Medical Press, 2020)
Abd Kakhar Umar, Maria Butarbutar, Sriwidodo Sriwidodo, Nasrul Wathoni Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor 45363, IndonesiaCorrespondence: Nasrul Wathoni; Sriwidodo SriwidodoDepartment of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor 45363, IndonesiaTel +6222 842 888888Email nasrul@unpad.ac.id; sriwidodo@unpad.ac.idAbstract: Film-forming sprays offer many advantages compared to conventional topical preparations because they can provide uniform drug distribution and dose, increased bioavailability, lower incidence of irritation, continuous drug release, and accelerated wound healing through moisture control. Film-forming sprays consist of polymers and excipients that improve the characteristics of preparations and enhance the stability of active substances. Each type of polymer and excipient will produce films with different features. Therefore, the various types of polymers and excipients and their evaluation standards need to be examined for the development of a more optimal form of film-forming spray. The selected literature included research on polymers as film-forming matrices and the application of these sprays for medical purposes or for potential medical use. This article discusses the types and concentrations of polymers and excipients, sprayer types, evaluations, and critical parameters in determining the sprayability and film characteristics. The review concludes that both natural and synthetic polymers that have in situ film or viscoelastic properties can be used to optimise topical drug delivery.Keywords: film-forming solution, film-forming polymer, topical drug delivery